Positive effect of Balint group on burnout and self-efficacy of head nurses in China: a randomized controlled trial - Shan, Qu; Leonhart, Rainer; Zhijuan, Xie; Minjie, Zheng; Xinxin, Shi; Xinzhu, Bai; Xiangyan, Kong; Fritzsche, Kurt (Frontiers in Psychiatry, 2024)
Background: Burnout is common among nurses and can lead tois related to negative outcomes of medical care. This study aimed to explore the effectiveness of Balint groupsBalint group activities in togroups to reduce burnout reduction among innurse leadersheadin head nurses in a Chinese hospital. Methods: This was a randomized controlled trial with a pre-and post-test. A total of 80 nurse leadershead nurses were randomly assigned to either a Balint group (n=40) or a non-Balint groupcontrol group (n=40). Participants participated in the Balint group underwent Balint training for a period of three months. Participants in both groups completed the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) and the General Self-Efficacy Scale (GSES) atScale at the beginning and end of the study. Balint group members also completed the Group Climate Questionnaire-Short Form. Results: In the Balint group, 33 participants attended all sessions of Balint groupsthe Balint intervention, while the 40 participants in the control groupnon-Balint group had no intervention. Analysis of variance with repeated measures demonstrated a statistically significant difference on the Maslach Burnout InventoryMBI subscale of sense of personal accomplishmentachievement (F = 9.598, p = 0.003) between the Balint and non-Balint groupcontrol groups. However, there were no significant differences between the groups on the MBI subscales of emotional exhaustion (F= 0.110, p= 0.740) and depersonalization (F = 0.75, p = 0.387), and the General Self-Efficacy ScaleGSES (F = 0.709, p = 0.403). Conclusions: Balint groups activity helped reduce burnout among nurse leadershead nurses in terms of personal accomplishmentachievement.